2013
DOI: 10.1136/bmjopen-2013-002934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-protein diet on kidney function in diabetic nephropathy: meta-analysis of randomised controlled trials

Abstract: ObjectiveTo evaluate the effect of low-protein diet on kidney function in patients with diabetic nephropathy.DesignA systematic review and a meta-analysis of randomised controlled trials.Data sourcesMEDLINE, EMBASE, Cochrane Library, ClinicalTrials.gov, International Standard Randomised Controlled Trial Number (ISRCTN) Register and University Hospital Medical Information Network-Clinical Trials Registry (UMIN-CTR) from inception to 10 December 2012. Internet searches were also carried out with general search e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 43 publications
7
71
1
4
Order By: Relevance
“…While the classic Cochrane review did not suggest an effect of LPDs on CKD progression, both the older study from Pedrini and the newer one from Nezu (including more cases in early CKD stages) suggest that, on the contrary, LPDs may have a favourable effect, in accordance with what was observed in non-diabetic patients [50,51,52]. …”
Section: Discussionmentioning
confidence: 63%
“…While the classic Cochrane review did not suggest an effect of LPDs on CKD progression, both the older study from Pedrini and the newer one from Nezu (including more cases in early CKD stages) suggest that, on the contrary, LPDs may have a favourable effect, in accordance with what was observed in non-diabetic patients [50,51,52]. …”
Section: Discussionmentioning
confidence: 63%
“…Low protein intake was defined as 0.6-0.8 g/kg/day and regular protein intake as 1.0-1.6 g/kg/day. 145 Substituting soy protein for animal protein may also be beneficial in diabetics with proteinuria but studies have not been consistent. 146 A number of alternative medicine supplements have also been studied (Table 3).…”
Section: Lifestyle Diet and Alternative Medicinementioning
confidence: 99%
“…Nezu et al showed that an LPD for diabetic nephropathy improves the estimated glomerular filtration rate when patients adhere to a protein-restricted diet [11]. However, LPD adherence is often poor [3,11], which has contributed to the controversial results of previous clinical studies. In addition, the amount of protein restriction would be expected to be important for renoprotection.…”
Section: Introductionmentioning
confidence: 99%